ANTIBODY RESPONSE OF RABBITS TO COMBINED HEMORRHAGIC SEPTICEMIA AND FOOT & MOUTH DISEASE VIRUS VACCINE - I. Altaf; M. Siddique; K. Muhammad; M. Irshad; M. Z. Khan; A. A. Anjum; M. Kamran (Journal of Animal and Plant Sciences, 2012)
Infectious diseases particularly Foot and Mouth Disease (FMD) & Hemorrhagic septicemia (HS) are challenge for livestock and dairy industry all over the world and cause great economic losses. Vaccination programs using monovalent vaccines against the diseases are effective but the repeated vaccination induces stress to the animals and increase cost of vaccination for the farmer. In this study, efficacy of bivalent FMD+HS vaccine was compared to monovalent FMD and HS vaccines in rabbits. Previously isolated and characterized FMD virus “O” serotype and Pasteurella multocida were used in the experimental design. Alum precipitated FMD, HS and FMD+HS vaccines were prepared and injected in experimental rabbits (6 months of age) at 0 and 14th day. The serum samples were collected on 0, 14, 28, 35 and 48 days post-priming. Antibody titer was measured by Virus Neutralization (V/N) for FMD “O” virus and Indirect Hemagglutination (IHA) test for lipopolysaccharide (LPS) of Pasteurella multocida. The results showed that peak level of Geometric mean antibody titer (50.8 VN units & 40.3 IHA units) was obtained on 35th day in both the monovalent FMD and HS vaccine, respectively whereas in bivalent FMD+HS vaccine peak level of GMT antibody titer (161.3 VN units +50.8 IHA units) was detected on 48th days post-priming. It is concluded that combine bivalent vaccine produced better antibody titer that persisted for longer time.
Keywords: Food and Mouth Disease; Pasteurella multocida; Monovalent; Bivalent